2020
DOI: 10.3389/fpls.2020.01158
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Management Practices to Decrease Deoxynivalenol Contamination in Soft Red Winter Wheat

Abstract: Fusarium graminearum, the major causal agent of Fusarium head blight (FHB) of wheat (Triticum aestivum) in the U.S., can produce mycotoxins, such as deoxynivalenol (DON), during infection. Contamination of wheat grain with DON is a major concern for wheat producers and millers, and the U.S. Food and Drug Administration (FDA) has set advisory levels for DON in finished wheat products for human and animal consumption. Practices utilized to manage FHB and DON contamination include planting wheat cultivars with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Differences in grain yield between the two seeding rates were previously reported by Rod et al. (2020). Differences between the in‐furrow phosphorus treatment and the non‐treated control were determined using analyses of variance (SAS version 9.4; PROC MIXED; seeding rate was specified as fixed effects; site, year, and rep(year×site) were specified as random effects).…”
Section: Figuresupporting
confidence: 65%
See 1 more Smart Citation
“…Differences in grain yield between the two seeding rates were previously reported by Rod et al. (2020). Differences between the in‐furrow phosphorus treatment and the non‐treated control were determined using analyses of variance (SAS version 9.4; PROC MIXED; seeding rate was specified as fixed effects; site, year, and rep(year×site) were specified as random effects).…”
Section: Figuresupporting
confidence: 65%
“…For the increased seeding rate, Rod et al. (2020) previously reported that grain yield increased an average of 4 bu acre −1 when seeding rates were increased to 56 plants ft −2 . The risk analysis found that yield increased by at least 1 bu acre −1 63% of the time and by at least 5 bu acre −1 42% of the time when seeding rate was increased from 35 plants ft −2 to 56 plants ft −2 for wheat planting that was delayed by at least 1 month (Figure 2).…”
Section: Figurementioning
confidence: 99%
“…a Early and normal correspond to the planting timing. Early planting occurred after wheat was harvested at 20 to 22% grain moisture; normal planting timing occurred after wheat was harvested at 13 to 15% grain moisture (Rod et al, 2020).…”
Section: Core Ideasmentioning
confidence: 99%
“…Six management practices were examined at two planting timings (Table 2). The planting timings succeeded two soft red winter wheat harvest timings: 20 to 22% wheat grain moisture (early) and 13 to 15% wheat grain moisture (normal) (Rod, 2020;Rod et al, 2020). The six management treatments consisted of different combinations of seeding rates (150,000 or 225,000 seeds acre −1 ), seed treatments (treated or nontreated), and foliar pesticide (economic threshold or prophylactic R3 applications) (Table 2).…”
Section: Experimental Treatmentsmentioning
confidence: 99%
“…Given the current global warming associated with increased temperatures, major epidemics of FHB are occurring. Thus, proper cultivation schemes and field management are essential to alleviate its threat ( Bai and Shaner, 2004 ; Vaughan et al, 2016 ; Ma et al, 2020 ; Rod et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%